Integrin-α9β1 as a Novel Therapeutic Target for Refractory Diseases: Recent Progress and Insights - Xu, Shihan; Zhang, Tingwei; Cao, Zhengguo; Zhong, Wenjie; Zhang, Chuangwei; Li, Han; Song, Jinlin (Frontiers in Immunology, 2021)
Integrins refer to heterodimers consisting of subunits α and β. They serve as receptors on cell membranes and interact with extracellular ligands to mediate intracellular molecular signals. One of the least-studied members of the integrin family is integrin-α9β1, which is widely distributed in various human tissues and organs. Integrin-α9β1 regulates the physiological state of cells through a variety of complex signalling pathways to participate in the specific pathological processes of some intractable diseases. In recent years, an increasing amount of research has focused on the role of α9β1 in the molecular mechanisms of different refractory diseases and its promising potential as a therapeutic target. Accordingly, this review introduces and summarises recent research related to integrin-α9β1, describes the synergistic functions of α9β1 and its corresponding ligands in cancer, autoimmune diseases, nerve injury and thrombosis and, more importantly, highlights the potential of α9β1 as a distinctive target for the treatment of these intractable diseases.